Gross negligence 'medical' manslaughter in Ireland: Legal context and clinician concerns. (December 2021) - Tumelty, Mary-Elizabeth; Spain, Eimear
In recent years, the prospect of the criminal prosecution of medical practitioners for patient safety incidents resulting in fatality which occur in the course of clinical practice has caused heightened anxiety among medical practitioners, particularly in England and Wales, where a number of high-profile cases have raised public consciousness of this issue. The full impact of this landscape on individual practitioners and the delivery of healthcare has yet to be ascertained, although research suggests that medical practice has been impacted. Of particular interest is the phenomenon of defensive medicine which occurs where physicians adopt assurance and/or avoidance behaviours in an attempt to minimise the risk of medical negligence litigation and/or to avoid complaints to regulatory bodies. While defensive medicine is traditionally conceived of in a civil context, the possibility of criminal prosecution for patient safety incidents resulting in fatality may also result in alterations to medical practice. Drawing on the findings of an empirical study (a survey), this research sought to explore the impact, if any, of the threat of criminal prosecution on surgical practice in the Republic of Ireland, including a potential rise in defensive practice.